Effect of total glycosides of Cistanche deserticola on the energy metabolism of human HepG2 cells - Feng, Duo; Zhou, Shi-qi; Zhou, Ya-xi; Jiang, Yong-jun; Sun, Qiao-di; Song, Wei; Cui, Qian-qian; Yan, Wen-jie; Wang, Jing (Frontiers in Nutrition, 2023)
To study the anti-tumor effect of Cistanche deserticola Y. Ma, HepG2 cells were treated with 0, 3.5, 10.5, 21, 31.5, and 42 μg/ml of total glycosides (TG) from Cistanche deserticola. The HepG2 cell survival rate and 50% inhibition concentration (IC50) were detected using the CCK-8 method, and the level of reactive oxygen species (ROS) was detected by using a DCFH-DA fluorescence probe. Finally, a Seahorse XFe24 energy analyzer (Agilent, United States) was used to detect cell mitochondrial pressure and glycolytic pressure. The results showed that TG could reduce the survival rate of HepG2 cells and that the IC50 level was 35.28 μg/ml. With increasing TG concentration, the level of ROS showed a concentration-dependent upward trend. Energy metabolism showed that each dose group of TG could significantly decline the mitochondrial respiratory and glycolytic functions of HepG2 cells. In conclusion, TG could significantly inhibit the mitochondrial respiration and glycolysis functions of HepG2 cells, increase the level of ROS, and inhibit cell proliferation. Thus, this experiment pointed out that Cistanche deserticola can be used as a source of anti-cancer foods or drugs in the future. However, further studies on its mechanisms and clinical applications are needed.